2011
DOI: 10.1258/ijsa.2011.011262
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care HIV testing at antenatal care and maternity sites: experience in Battambang Province, Cambodia

Abstract: Worldwide elimination of HIV transmission from mother-to-child is theoretically achievable. In Cambodia, antenatal care (ANC) prevalence has dropped from 1.6% (2003) to 0.71% (2009). However, success in minimizing vertical transmission has been limited by low testing uptake at ANC and delivery. We trained midwives in counselling and performance of an HIV rapid test, incorporated point-of-care testing into routine antenatal and maternity services and determined acceptability, feasibility, accuracy, cost and yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 10 publications
(6 reference statements)
0
22
0
1
Order By: Relevance
“…Human immunodeficiency virus (HIV) rapid tests have been a successful intervention to improve healthcare access and outcomes of pregnant women. 3,4,5,6,7,8 HIV rapid testing can allow timely initiation of antiretroviral therapy (ART) and facilitate linkages to care for HIV-infected women. 3,4,5,6,7,8 However, to ensure sustainability and accuracy of HIV testing services, HIV rapid tests must meet certain standards.…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) rapid tests have been a successful intervention to improve healthcare access and outcomes of pregnant women. 3,4,5,6,7,8 HIV rapid testing can allow timely initiation of antiretroviral therapy (ART) and facilitate linkages to care for HIV-infected women. 3,4,5,6,7,8 However, to ensure sustainability and accuracy of HIV testing services, HIV rapid tests must meet certain standards.…”
Section: Introductionmentioning
confidence: 99%
“…Of the six studies eligible for data extraction, four were cross-sectional studies (41–44) and two were case-control studies (45, 46). All included studies were published between and 2001 and 2015 and included HIV-infected women with the objective of assessing the impact of HIV-related POC diagnostics on maternal outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 167 were HIV-infected women. Four out of the six of the included studies were carried out in urban areas (41, 42, 44, 46). Of the remaining two studies, one was carried out in a rural area (45) and the other in a semi-urban area (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Cambodia demonstrated that 95.4% and 99.4% of women in antenatal clinics and labour, respectively, accepted rapid HIV testing 30. In a study from Chiang Rai Province, Thailand, 96.8% of women in antenatal and postnatal settings were satisfied with the rapid testing process and 78.7% of women said they preferred this process to conventional HIV testing 36.…”
Section: Commentarymentioning
confidence: 99%